(3aVGFd heSGFd ddeQJVis - (3GdeQJVjs ((3eMeO Hf eMeO Ydi s)
(3ChdgG (B:s
(3eSFdI NQLJ ai TYHGf SfI NeS YTQI hCQHYeGFI LhGHkG Yf eSFdI hQOJ Yf NQSGf abGd GdTjYI GdEeGejI JfcQ GdeSM Ydi GdNajf s
(3BNQgG (B:s
(3hgPg LedI ebfYI ai gPg GdeSFdI hGddg GdeSJYGf hHg GdJhajb JeJ GdeSGFd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B14s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(369) s
Keywords: (3GdeLGejYs